The German Paths of Peter Pan: On German Mediation in the First Polish Translation of J.M. Barrie’s Peter Pan in Kensington Gardens - Wieczorkiewicz, Aleksandra (Porównania, 2023)
The article presents the results of the analysis of the first Polish translation of J.M. Barrie’s Peter Pan in Kensington Gardens authored by Zofia Rogoszówna (Przygody Piotrusia Pana, 1913) as a mediated translation. Based on a method inspired by textual criticism, inside the framework of indirect translation studies, I argue that Rogoszówna’s version was based on the German translation Peter Pan im Waldpark (1911) by Irmgard Funcke. The article also addresses the questions of how, due to the multistage transmission of the text, the profile of its projected addressee changes; how, by means of translational shifts, translators “adjust” the original to the sensibilities of the readers (by domestication or cultural universalisation); how, therefore—through the prism of linguistic transfer—thinking about the child and the role of juvenile literature in England, Germany and Poland of the early twentieth century can be characterised.